2011
DOI: 10.1039/c1cc11289a
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest chemistry at interface for photoswitchable bioelectrocatalysis

Abstract: Photoswitchable bioelectrocatalysis of glucose with glucose oxidase in an "On-Off" state is fabricated from host-guest chemistry at an interface by using the photocontrolled reversible immobilization and detachment of ferrocene-labeled redox-polymer as mediator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Wan et al . designed a photoswitchable‐bioelectrocatalytic system using host‐guest chemistry . Azobenzene and ferrocene were used as light and redox stimuli respectively.…”
Section: Applications Of Ferrocene‐based Electro and Photo Responsivementioning
confidence: 99%
See 2 more Smart Citations
“…Wan et al . designed a photoswitchable‐bioelectrocatalytic system using host‐guest chemistry . Azobenzene and ferrocene were used as light and redox stimuli respectively.…”
Section: Applications Of Ferrocene‐based Electro and Photo Responsivementioning
confidence: 99%
“…Azobenzene and ferrocene were used as light and redox stimuli respectively. It has been reported that this kind of systems can be used as optoelectronics and photoswitchable biofuel cells (Figure ) …”
Section: Applications Of Ferrocene‐based Electro and Photo Responsivementioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and co‐workers fabricated a photo‐switchable bioelectrocatalysis using a ferrocene‐labeled redox‐polymer as mediate, which can be reversibly immobilized on photo‐responsive azobenzene‐modified surfaces controlled by light. Firstly, poly(acrylic acid) polymer grafted with β‐CD was assembled onto azobenzene‐containing self‐assembled monolayer modified gold surface through host–guest interactions between azobenzene and β‐CD.…”
Section: Photochromism In Artificial Supramolecular Self‐assembling Smentioning
confidence: 99%
“…In addition, azobenzene-CD SAMs have been employed to mediate the oxidation of glucose by GOx [258] and immobilize and release proteins on demand [259]. Interestingly, the azobenzene-CD SAM designed to control protein immobilization was not only able to respond to light but also to changes in pH.…”
Section: Samsmentioning
confidence: 99%